ESTABLISHMENT OF A TRADITIONAL VILLAGE REGULATION CONCERNING TO THE MANAGEMENT OF DOGS AND CATS IN THE TRADITIONAL SEGA VILLAGE, BUNUTAN, KARANGASEM BALI - Velyniawati, Putu; Girardi, Janice; Subrata, I Made; Januraga, Pande Putu; Utami, Ni Wayan Arya; Purnama, Sang Gede; Swacita, Ida Bagus Ngurah; Dawdoya, Anne; Harjana, Ngakan Putu Anom; Agustina, Kadek Karang (Buletin Veteriner Udayana, 2023)
Human deaths due to rabies that occurred in the Sega traditional village area in 2018 made the village consider that rabies is a threat to the community in the Sega traditional village area. The presence of the dharma program in 2020 in Sega traditional villages helps raise public awareness regarding the dangers of rabies and the importance of vaccination in the prevention and control of rabies. The establishment of an internal regulation in the village is considered necessary and important to be drafted to assist and support efforts to control rabies in the area of ??the Sega traditional village. Perarem pangele began to be compiled using the FGD (Focus Group Discussion) method together with the internal parties of the traditional village consisting of the traditional bendesa, prajuru and community leaders. The considerations of legal experts and academics from the Dharma Program were also included in perfecting the draft perarem pangele. The results of the Perarem draft were then consulted with related institutions and revised in accordance with the rules, systematic grammar. This Perarem has been issued with registration number P/0038/1206/043/07/DPMA/2022 with the title Perarem Pangele No. 07 of 2021 concerning Procedures for Caring for Dogs and Cats in Sega Traditional Village, Bunutan Village, Abang District, Karangasem Regency. 4 important points contained in this pangele perarem are related to the rights and obligations of dog and cat owners, how to maintain dogs and cats, how to handle dogs and cats as well as prohibitions and sanctions for violations. Further socialization needs to be done to implement this pangele perarem.